Diseño de carrocería para el servicio público urbano de taxis en Bogotá (2024)
Industrial design is an essential field in the creation of products and solutions timely actions that systematically influence construction, planning and development of products within the market, both for the present and for the future (Infinita Industrial Consulting, 2021). Automotive design shares a close relationship with the industrial design in similar approaches when conceiving a new product within of the market, from a conceptual creation process to its production and introduction within a specific market. (Mextudia, n.d.)